ADRENAL MEDULLA OF WHITE SVVISS NIICE (Mus Musculus) AND LAYING HENS (Gallus Domesticus) - Al Saffar, F .J. (The Iraqi Journal of Veterinary Medicine, 2021)
Adult white swiss mice and- laying hens were used to study the adrenal medulla. Samples of adrenal glands were collected and fixed in formal dichrornate solution and six micron thick sections were stained by Harris H & E. Light microscopic observations reveal that adrenal medulla of both White Swiss mice and laying hens were built up of two types of chromaffin cells, without any characteristic features of zonation. In laying hens : our data revealed that mednllary tissue was intermingled with the cortical one and the adrenaline cells were mainly distributed in the subcapsular region, While large central vein was seen in the medulla of white Swiss mice surrounded mainly by noradrenaline cell.